Mario Vargas Llosa - Castro, Juan E. De, 1959- (Ipswich, Massachusetts : Salem Press, a division of EBSCO Information Services, Inc. ; Amenia, NY : Grey House Publishing, 2014)
Provides an introduction to Mario Vargas Llosa and the critical discussions surrounding his work --
On Mario Vargas Llosa / Juan E. De Castro -- Biography of Mario Vargas Llosa / Juan E. De Castro -- Authoritarianism, rebellion, and the father figure in the fictions of Vargas Llosa / t t Dissonant worlds: Mario Vargas Llosa and the aesthetics of the total novel / Mark D. Anderson -- Mario Vargas Llosa and his discontents / Will H. Corral.
Includes bibliographical references (pages 251-256) and index.
Keywords: Vargas Llosa, Mario, -- 1936-2025 -- Criticism and interpretation; Peruvian fiction -- History and criticism; Spain -- In literature; Vargas Llosa, Mario, -- 1936-2025